Para-s/cite, Part I. The Parasite - Constantine Nakassis (Semiotic Review, 2013)
Through the idiom of the parasite, this two-part essay explores the citation, its performativities, and its limits. Part I, “The Parasite,” explores the role of the parasite in Jacques Derrida’s engagement with speech act theory; in particular, his discussion of citationality in Limited Inc (1988). I suggest that the criterial feature of the citation—its reflexivity about what Derrida calls citationality—, while not talked about by Derrida, is poetically, even performatively, demonstrated by his text. Focusing on the reflexive semiotics of the citation, I argue that the performative entailments of parasites and citations turn on their ability to decenter and bracket, even as they embrace and re-present, that which they cite/parasite. And further, that through this double motion new social horizons of semiotic possibility are opened up.